تطوير استخدام قاموس الجيب لإتقان المفردات في مدرسة الحكمة الابتدائية الإسلامية المتكاملة تشيلانداك - Hasanah, Uswatun Hasanah; Muhbib Abdul Wahab; Wati Susiawati (Penerbit Minhaj Pustaka, 2025)
The researcher chose this topic in response to the urgent need for a practical and portable learning tool to help students master Arabic vocabulary. This need arises due to challenges such as students’ weak vocabulary skills, which result from relying solely on school lessons, and their boredom with using large and heavy textbooks. The objectives of this research are: 1) to develop a pocket dictionary for Arabic vocabulary learning for 4th-grade students, 2) to examine its effectiveness before and after implementation, and 3) to assess the quality of the developed product. The researcher used a Research and Development (R&D) approach with both quantitative and qualitative methods, based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through questionnaires, interviews, observations, and documentation. The results showed that the pocket dictionary was effective in helping students understand and use vocabulary by presenting the words in a structured and concise format, supported by colors, symbols, and illustrations that enhance understanding and motivation. It also promotes student autonomy, as it can be used both in and outside the classroom—especially in learning environments with limited access to technology such as smartphones or the internet. Therefore, the pocket dictionary is considered an effective and comprehensive educational tool to support vocabulary learning among 4th-grade students.